(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In the area of contemporary construction the modules of each material and the units are very different. If harmony can be introduced lots of wastage can be avoided. Because in this era of climate change the construction industry is one of the biggest unsustainable and pollutant industries. This paper aims to discuss the unit of the least module for contemporary construction. The study is supported by standards and case studies and various practicing modules. Drawings are made the prove the least module for construction of housing of LIG, MIG, and HIG units.